1995
DOI: 10.3382/ps.0741356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-Tocopherol on Antioxidants, Lipid Peroxidation, and the Incidence of Pulmonary Hypertension Syndrome (Ascites) in Broilers

Abstract: Research has demonstrated a compromised antioxidant capacity in broilers with pulmonary hypertension syndrome (PHS). Thus, the objective of the present study was to assess the effects of vitamin E on PHS-induced mortality, tissue antioxidants, and plasma lipid peroxides in male broilers. Control broilers were provided normal ventilation but others, maintained under low ventilation conditions to induce PHS, were randomly assigned to nonimplanted (NI), placebo (PL), or vitamin E (VE) implanted groups. The VE imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…For example, the antioxidant dimethylthiourea inhibits right heart dysfunction usually induced by a 10-day exposure to hypoxia in rats (54,70,73) and significantly abrogates the pulmonary hypertensive response (54). PH syndrome in avian species, with reduced respiratory chain coupling, inefficient use of oxygen, and higher generation of ROS (25,57,126), is successfully treated by implanting nonenzymatic antioxidant pellets of vitamin E after chickens hatch (20). In vitamin E-treated chickens, the incidence of avian PH syndrome is decreased and antioxidant capacity increased (20).…”
Section: Ros and Antioxidants In Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the antioxidant dimethylthiourea inhibits right heart dysfunction usually induced by a 10-day exposure to hypoxia in rats (54,70,73) and significantly abrogates the pulmonary hypertensive response (54). PH syndrome in avian species, with reduced respiratory chain coupling, inefficient use of oxygen, and higher generation of ROS (25,57,126), is successfully treated by implanting nonenzymatic antioxidant pellets of vitamin E after chickens hatch (20). In vitamin E-treated chickens, the incidence of avian PH syndrome is decreased and antioxidant capacity increased (20).…”
Section: Ros and Antioxidants In Pulmonary Hypertensionmentioning
confidence: 99%
“…PH syndrome in avian species, with reduced respiratory chain coupling, inefficient use of oxygen, and higher generation of ROS (25,57,126), is successfully treated by implanting nonenzymatic antioxidant pellets of vitamin E after chickens hatch (20). In vitamin E-treated chickens, the incidence of avian PH syndrome is decreased and antioxidant capacity increased (20). Similarly, N-acetyl-l-cysteine, which serves as a precursor to the nonenzymatic antioxidant glutathione, reduces PH, right ventricular hypertrophy, and pulmonary vascular media thickening in a hypoxia-induced rodent model of PH (55).…”
Section: Ros and Antioxidants In Pulmonary Hypertensionmentioning
confidence: 99%
“…Early studies conducted in the mid-1990s suggested the beneficial effects of antioxidants on lipid peroxidation and the incidence of pulmonary hypertension syndrome in broilers. 1 A growing number of in vitro studies have reported beneficial effects of retinoids on cell migration, proliferation, apoptosis, matrix remodeling, fibrinolysis, coagulation, and inflammation, all of which are involved with vascular disease. 2 There is a rich literature on human PAH oxidative stress showing associations between increased oxidant-injury markers and poorer clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E is a well-recognized natural antioxidant used for the prevention of biological oxidation, and was shown to reduce mortality due to ascites (Bottje et al, 1995). However, the addition of high concentrations of VE increases the cost of the diet (Kennedy et al, 1992), leading to the search of new more affordable sources of antioxidant compounds, such as grape seed extract (GSE).…”
Section: Lipid Peroxidation In the Plasma Lungs Heart And Liver Of mentioning
confidence: 99%
“…Bakonyi & Radak (2004) reported that exposure to high altitude increases the formation of reactive oxygen species (ROS) and reactive nitrogen species, and ROS cause lipid peroxidation in heart and liver of broilers (Díaz-Cruz et al, 1996). Bottje et al (1995) reported that oxidative stress is associated with AS. Rodríguez-Ortega et al (2014) observed that ad libitum feeding decreases antioxidant activity in lungs, heart, and liver of broilers.…”
Section: Introductionmentioning
confidence: 99%